(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Detection of benign parapharyngeal mass is very crucial for the management of the patients. Objective: The purpose of the present study was to evaluate the CT scan for the detection of benign parapharyngeal mass. Methodology: This cross-sectional study was carried out in the Department of Radiology and Imaging at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from July 2009 to April 2011 for a period of around two years. All the clinically suspected cases of parapharyngeal space mass lesions attended in the Otolaryngology and Radiology & Imaging department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka were enrolled in this study. The patient in this study was evaluated according to the management plan for surgery followed in Otolaryngology department. The histopathology was performed by the histopathologist of the Department of Pathology at BSMMU, Dhaka, Bangladesh. All patients were undergone CT examination of neck and the comparison of the findings was done with the histopathology results. Result: A total number of 50 patients were recruited for this study after fulfilling the inclusion and exclusion criteria. Mean (±SD) age of the patients was 37.76 (±14.82). Sensitivity of CT to diagnose benign parapharyngeal mass was 92.1%, specificity 83.3%, positive predictive value 94.6%, negative predictive value 76.9% and accuracy 90.0%. The area under the curve value was calculated and was found 0.142 (95% CI 0.000 to 0.286) (p=0.000). Conclusion: In conclusion the sensitivity and specificity of CT scan for the detection of benign parapharyngeal mass lesion is very high. Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 118-121